2022
DOI: 10.1108/jocm-11-2021-0356
|View full text |Cite
|
Sign up to set email alerts
|

Examining resilience: the role of creativity-oriented high-performance work practices and role clarity

Abstract: PurposeThe paper aims to highlight the understated role of creativity in R&D organizations by exploring the effect of creativity-oriented high-performance work practices (CHPWPs) on resilience. The moderator effect of role clarity (RC) on the association between CHPWPs and resilience is examined.Design/methodology/approachThe study proposes a simple moderation model to understand the relationship, and specifically hierarchical regression analysis (SPSS 22.0) and SPSS PROCESS Macro has been used to test the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…Mafabi et al (2015) show that creative climate has a significant association with innovation and organisational resilience. Aparna & Sahney (2022) found that creativity significantly improves resilience. Qualitative study by Protogerou et al (2022) explored more deeply the conceptual framework of firm resilience.…”
Section: Creativity and Sme Resiliencementioning
confidence: 99%
See 3 more Smart Citations
“…Mafabi et al (2015) show that creative climate has a significant association with innovation and organisational resilience. Aparna & Sahney (2022) found that creativity significantly improves resilience. Qualitative study by Protogerou et al (2022) explored more deeply the conceptual framework of firm resilience.…”
Section: Creativity and Sme Resiliencementioning
confidence: 99%
“…Consistent with the principles of the resource-based theory (RBT), an organization's capacity to exhibit resilience is a critical resource that can be systematically cultivated and nurtured over time. The capacity to withstand and recover from disruptive circumstances is contingent upon both the individual and the organization (Aparna et al, 2022). It is imperative that its members possess individual resilience in order for an organization to achieve resilience (Lengnick-Hall et al, 2011).…”
Section: Digital Leadership and Smes Resiliencementioning
confidence: 99%
See 2 more Smart Citations
“…These issues are especially significant in firms where R&D is paramount. Aparna and Sahney (2023) therefore explore the relationships further in a study of R&D organizations in India. Government investment into R&D has been relatively stagnant over recent decades and not in proportion to India's economic growth.…”
Section: Indian Study and Findingsmentioning
confidence: 99%